Measuring herpes zoster, zoster-associated pain, post-herpetic neuralgia-associated loss of quality of life, and healthcare utilization and costs in Thailand - Kobkul Aunhachoke (2018)
Objectives This study aimed to measure the herpes zoster-associated burden of illness, healthcare utilization, and costs among Thai patients. Methods This prospective cohort study of 180 patients aged ≥50years and healthy, or ≥20years and immunosuppressed, with zoster rash, was conducted in Bangkok and its environs, Thailand, during 2007-2008. Each patient was followed for sixmonths for zoster-associated rash, pain, quality of life (QoL), and healthcare utilization and costs. Results A total of 180 subjects were enrolled in the study. Their mean±standard deviation (SD) age was 58.9±13.8years. Of the 180 patients enrolled, 138 (76.7%), 34 (18.9%) and eight (4.4%) patients were elderly, HIV-infected, and receiving immunosuppressive agents, respectively; 35 (19.4%) had post-herpetic neuralgia (PHN), and 13 (7.2%) had zoster ophthalmicus. The severity of zoster pain was moderately highly correlated with activities of daily living (ADL), at 0.68≤ρ≤0.76. Most patients required only one or two outpatient visits. The mean±SD total of direct healthcare costs was 3083.4±5047.0 Thai baht or ∼1.1% of annual income per capita. Conclusions Herpes zoster contributes a significant burden of illness to both patients and the wider community. © 2011 The International Society of Dermatology.